2013
DOI: 10.1371/journal.pone.0081365
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Genetic Differentiation among Blackcaps (Sylvia atricapilla) with Divergent Migratory Orientations in Europe

Abstract: Migratory divides are thought to facilitate behavioral, ecological, and genetic divergence among populations with different migratory routes. However, it is currently contentious how much genetic divergence is needed to maintain distinct migratory behavior across migratory divides. Here we investigate patterns of neutral genetic differentiation among Blackcap (Sylvia atricapilla) populations with different migratory strategies across Europe. We compare the level of genetic divergence of populations migrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 63 publications
3
35
1
Order By: Relevance
“…It has been suggested that migratory behaviour not only shapes population genetic structure across migratory flow patterns, but also at an individual level as a result of microhabitat choice . However, consistent with our results, previous genetic studies failed to show a clear genetic structure for blackcap populations (Mettler et al, 2013), which may be because the use of neutral genetic markers is not sufficient to detect the finescale genetic structure of populations (Reed & Frankham, 2001). This also strongly suggests that the genetic divergence is recent and that gene flow between populations can persist (P erez-Tris et al, 2004).…”
Section: No Small-scale Genetic Structuresupporting
confidence: 82%
See 1 more Smart Citation
“…It has been suggested that migratory behaviour not only shapes population genetic structure across migratory flow patterns, but also at an individual level as a result of microhabitat choice . However, consistent with our results, previous genetic studies failed to show a clear genetic structure for blackcap populations (Mettler et al, 2013), which may be because the use of neutral genetic markers is not sufficient to detect the finescale genetic structure of populations (Reed & Frankham, 2001). This also strongly suggests that the genetic divergence is recent and that gene flow between populations can persist (P erez-Tris et al, 2004).…”
Section: No Small-scale Genetic Structuresupporting
confidence: 82%
“…A total of 17 microsatellite markers developed for the blackcap were used (Segelbacher et al, 2008;Mettler et al, 2013). F-primers were fluorescently labelled using the commercially available dyes, FAM, VIC, NED, and PET.…”
Section: Pcr and Genotypingmentioning
confidence: 99%
“…Results here also indicate that different migration strategies, such as the use of different overwintering sites or the presence of non-migratory behaviour, can be maintained between populations despite high levels of gene flow [38], as also seen in the admixed populations of migratory and sedentary groups of broad-tailed hummingbirds in North America [59]. A similar lack of neutral genetic differentiation has been observed in other highly mobile, migrating species, such as hoverflies with different overwintering strategies in France [60] and blackcaps with different migratory behaviours and destinations in Europe [61].…”
Section: (B) Implicationsmentioning
confidence: 79%
“…; Mettler et al . ). Combined with over a decade of work on reproductive isolation between these subspecies groups (e.g., Ruegg & Smith ; Ruegg et al .…”
Section: Discussionmentioning
confidence: 97%